PENGARUH INDEPENDENSI DAN KOMPETENSI AUDITOR INTERNAL TERHADAP EFEKTIVITAS SISTEM PENGENDALIAN INTERN PADA PERUM DAMRI CABANG SAMARINDA - Emy Dwi Alvianti; Martinus Robert Hutauruk; Pantas Pangondian Pardede (University of Widya Gama Mahakam Samarinda, 2019)
The purpose of this study was to determine the independence and competence of internal auditors partially and simultaneously significant effect on the effectiveness of the internal control system at the Perum DAMRI Samarinda. Using quantitative research methods, with data collection techniques such as questionnaires. The sample in this study used a sampling technique; Nonprobability Sampling and includes saturated sampling, all populations are used as samples. The statistical method used in this study is multiple linear regression analysis using SPSS version 26 statistical aids.The results of this study indicate that partially the independence variable does not significantly influence the effectiveness of the internal control system of the Perum DAMRI Samarinda and the competence variable has a significant effect on the effectiveness of the internal control system of the of Perum DAMRI. Simultaneously independence and competence have a significant effect on the effectiveness of the internal control system at the Perum DAMRI Samarinda. Adjusted R Square value is 0.636, which means that all variables X1, X2 can explain 63.6% of the Y variable, while the remaining 36.4% can be explained by other variables or factors not tested in this study. Keywords - Independence, Competence, Internal Auditors, Effectiveness Internal Control System